Study Literature: Kegiatan Literasi Membaca dalam Mengasah Kemampuan Berpikir Kritis Peserta Didik Sekolah Dasar - Putri, Adelya Dinda Meyta Putri; Ulfa, Maria Ulfa; Rohmah, Desiana Maulidatur Rohmah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Literacy is the ability to understand, use and reflect on texts through direct involvement to gain experience to achieve certain goals. Activities in reading literacy require reasoning, understanding, and how to arrange words to make coherent and meaningful sentences. The problem that is still found today is the decline in interest in reading literacy among elementary school students. This research aims to provide insight into the benefits of reading literacy to expand knowledge and to hone critical thinking skills in elementary school students. The research method used in this article is a literature study by collecting national journals such as Sinta and Garuda journals, as well as international journals such as DOAJ from 2015 to 2023. The data obtained from the results of this research were then analyzed using content analysis techniques (Content Analysis). The results of data analysis show that the culture of reading literacy itself is closely related to fostering interest in reading in students, so students need to hone their critical thinking skills since elementary school